Communicative tools of journalists-bloggers on Belarusian TV: author’s narration - Tutenkov, Maxim S. (Journal of the Belarusian State University. Journalism, 2023)
The features of the use of communicative tools that contribute to the increase of the perlocative effect of the media text are considered. The communicative codes of the author’s narrative of journalists-bloggers, which acts as the core dominant of the information content, are determined. The analysed content of Belarusian journalists-bloggers by illocutionary parameters makes it possible to establish tools for achieving a communicative effect. It is established that in one author’s narrative there are different forms of narration and the types of narrators may overlap.